Effect of incorporation of filler particle on physical & mechanical properties and chemical changes in maxillofacial prosthetic silicone elastomer in local Malaysian weather - Twinkle, Aparna Barman (2021)
Maxillofacial prosthetic silicone elastomer (MFPSE) is the material of choice to refabricate the lost facial structure due to craniofacial defect. Still and all, MFPSE has some adverse effect which make the lifespan of the prosthesis limited. In the real-life scenario, the prosthesis which gets exposed in natural weather degrades earlier leads to replacement of the prosthesis frequently. Previously many researches had been conducted to improve the properties of MFPSE using filler particles in artificial weather. Therefore, the aim of this study is to explore the effect of nano fillers on surface roughness, tensile strength, percentage of elongation and the chemical changes of MFPSE subjected to outdoor weather. A total of 90 samples were prepared for this comparative in-vitro experimental study. Two different room temperature vulcanized (RTV) silicone (A-2006, A-103) were used to fabricate the samples and 2% TiO2 and 2% SiO2 by weight was incorporated with the experimental group. All the specimens were exposed in outdoor weather for four months in a custom-made exposure rack. After four months, specimens were tested. Surface roughness was tested by profilometer; tensile strength and percentage of elongation was measured by universal testing machine and the chemical changes was checked by Fourier-transform infrared (FTIR) spectrometer. Kolmogorov-Smirnov test was done to assess the normality of the data. For the property analysis two-way ANOVA was performed. The individual comparison, pairwise comparison and interaction effect was explored for both control and experimental group. In the individual comparison both factors, pairwise comparison and the interaction effect showed non-significant difference for surface roughness. A-103 with TiO2 showed the highest mean surface roughness. For tensile strength and percentage of elongation; both factors, pairwise comparison and interaction effect showed significant difference (P<.001). A-103 showed good tensile strength with both fillers and A-2006 with TiO2 showed the highest mean percentage of elongation. The FTIR spectra showed no extra or diminished peak between non-filler induced group and filler induced groups indicated that incorporation of nano fillers did not affect the chemical structure of MFPSE. As there were no chemical structural differences observed, therefore it can be suggested that A-103 with nano fillers had the capability of sustaining the surface smoothness and tensile strength in Malaysian weather and A-2006 was better for the percentage of elongation when incorporated with TiO2 and SiO2 filler in natural weathering condition.